2023
DOI: 10.1186/s12912-023-01257-1
|View full text |Cite
|
Sign up to set email alerts
|

Shiftwork sleep disorder and associated factors among nurses working at public hospitals in Harari Regional state and Dire Dawa Administration, Eastern Ethiopia: a cross-sectional study

Abstract: Background Shiftwork sleep disorder is one of the most common health-related effects of Shiftwork, particularly among healthcare workers. It is a chronic condition that is directly related to a person’s work schedule. In Ethiopia, although a mental health strategy is in place, little attention is given to studies that focus on shiftwork sleep disorders among nurses. This study aimed to determine the magnitude of shiftwork sleep disorder and associated factors among nurses working at public hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
2
1
0
1
Order By: Relevance
“…As for the present study’s result, current khat chewers have demonstrated three times higher odds of poor sleep quality than non-khat chewers. This finding aligns with studies performed in Yemen and Ethiopia ( 25 , 26 , 62 , 64 ). This could be due to the effect of khat.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As for the present study’s result, current khat chewers have demonstrated three times higher odds of poor sleep quality than non-khat chewers. This finding aligns with studies performed in Yemen and Ethiopia ( 25 , 26 , 62 , 64 ). This could be due to the effect of khat.…”
Section: Discussionsupporting
confidence: 92%
“…Female gender was associated with an increased odds of poor sleep quality. A similar finding was reported from a study conducted in Austria ( 60 ), Pakistan ( 19 ), Spain ( 18 ), Saudi Arabia ( 61 ), and Ethiopia ( 62 ). This could be due to increased household and family responsibilities in women, which is typically associated with women working for extended periods of time at night, which could affect their sleep quality.…”
Section: Discussionsupporting
confidence: 88%
“…These differences have been attributed to differences in healthcare systems, manpower, safer working conditions, sufficient resources, and a country being developed versus developing [38]. Others explained cultural factors that can vary from one country to another such as consumption of alcohol, caffeine, and energy drinks [43][44][45][46]. However, in a recent concept analysis, increased alcohol and caffeine intake was a consequence of poor sleep quality and not factors leading to poor sleep quality [47].…”
Section: Poor Sleep Qualitymentioning
confidence: 99%
“…Outro estudo realizado em hospitais do governo federal da Etiópia relatou que 49% dos enfermeiros que trabalhavam em turnos sofriam de problemas de sono (15) . Essas porcentagens são consideravelmente mais altas do que as relatadas por outros estudos realizados no Egito (31,1% dos enfermeiros com sonolência diurna) e na Etiópia (30,4% dos enfermeiros com distúrbio do sono no trabalho em turnos) (23)(24) . Outro estudo relatou que a diminuição da intensidade do turno pode reduzir a insônia entre enfermeiros de hospitais que trabalham em turnos rotativos (13) .…”
Section: Discussionunclassified